A Critical Discourse Analysis on Barack Obama’s Speech To the Congress - I Komang Sulatra; I Gusti Agung Sri Rwa Jayantini; Maksimianus Didimus Jehadu (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
Didimus Jehadu. Maksimianus 2020. A Critical Discourse Analysis on Barack Obama Speech to the Congress. English Study Program, faculty of Foreign Languages, Mahasaraswati Denpasar University. Supervisor: I Komang Sulatra S.SM. Hum; Co- supervisor: Dr. I Gusti Agung Sri Rwa Jayantini.S.S.M.Hum. The aims of the study are to find the Critical Discourse and language used by the Barack Obama Speech To the congress. Discourse is known as spoken or written language in a social context. The theory of types Critical discourse analysis (henceforth CDA) subsumes a variety of approaches towards the social analysis of discourse (Fairclough and Wodak 1997, Pecheuk M. 1982, Wodak and Meyer 2001. The objectives of this study were finding the structure of the next and describing the ideology that applied on Barack Obama Speech. This study used qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Based on the analysis, it is found that there are fiftythree Fourteen Barack Obama Speech there are structur Obama Speech Genre (26,41%), Framing (16,98%), Backgrounding/Foregrounding (3,77%), Presuposition (5,66%), Topicalisation (9,43%), Agency (3,77%), Delition/Ommision (1,88%), Insinuation (1,88%), Connotation (1,88%), Register (3,77%), Modality (11,32%), Opening (5,66%), Content(3,77%), Closing(3,77%). As the result of this analysis all the structural aspect of the theory are applied in Barack Obama Speech text to the congress, Can (1,1%), Could (1,1%), Would (3,5%), Must (20,2%), Will (64,2%), Should (9,5%).